2008
DOI: 10.1099/vir.0.83568-0
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral blood mononuclear cells represent a reservoir of bovine papillomavirus DNA in sarcoid-affected equines

Abstract: Bovine papillomaviruses of types 1 and 2 (BPV-1 and -2) chiefly contribute to equine sarcoid pathogenesis. However, the mode of virus transmission and the presence of latent infections are largely unknown. This study established a PCR protocol allowing detection of ¡10 copies of the BPV-1/-2 genes E5 and L1. Subsequent screening of peripheral blood mononuclear cell (PBMC) DNA derived from horses with and without BPV-1/2-induced skin lesions demonstrated the exclusive presence of E5, but not L1, in PBMCs of BPV… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
92
0
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(101 citation statements)
references
References 41 publications
5
92
0
4
Order By: Relevance
“…In veterinary medicine, previous studies have shown both the expression of E5 oncogene and the presence of E5 oncoprotein of BPV-2 in PBMCs (Brandt et al, 2008;Roperto et al, 2008). In human medicine, neither viral oncoproteins nor HPV-specific RNA are known to occur in PBMCs of PV-infected cancer patients (Pao et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…In veterinary medicine, previous studies have shown both the expression of E5 oncogene and the presence of E5 oncoprotein of BPV-2 in PBMCs (Brandt et al, 2008;Roperto et al, 2008). In human medicine, neither viral oncoproteins nor HPV-specific RNA are known to occur in PBMCs of PV-infected cancer patients (Pao et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…In cattle feeding on bracken fern, BPV-4 is associated with upper alimentary tract cancer. BPV-1 and BPV-2 are associated with both fibropapillomas in cattle and sarcoids in equids (Brandt et al, 2008;Nasir and Campo, 2008). BPV-2 infection in the presence of environmental carcinogens, such as ptaquiloside, a toxic principle of bracken fern (Pteridium aquilinum), has been associated with urinary bladder neoplasic lesions in adult cattle, in which chronic enzootic hematuria is the most important clinical sign (Hopkins, 1986;Campo et al, 1992;Campo, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Comparing levels of average heterozygosity, mean number of alleles per loci, effective number of alleles, mean range of microsatellite repeats and microsatellite variance estimates between a population of interest and its free-ranging counterpart are useful to determine loss of genetic variation. The appearance of sarcoid tumours in equids has been correlated with specific genetic haplotypes (Chambers et al 2003) with the involvement of BPV in the formation of sarcoid tumour in equids proven (Lohr et al 2005;Brandt et al 2008) and correlated with down-regulation of immune system genes (Ashrafi et al 2006;Yuan et al 2008). The only previous epizootic of sarcoid tumour reported was in horses, with four of the five affected individuals being members of a highly inbred herd (Ragland et al 1966).…”
Section: Discussionmentioning
confidence: 99%